Early warning system and coping strategies for pastoralists - Sileshi, Z.; Ebro, A.; Stuth, J.; Jamma, A.; Ndikumana, J. (Ethiopian Society of Animal Production, 2000)
The impact of drought can be governed by the timely and effective interventions of institutions. The challenge of drought needs strategic focus on three areas, viz, effective early warning system; coping mechanisms instituted in a timely manner; and recovery. Livestock early warning system therefore has to take into consideration these factors in order to develop reliable indicators based on the needs and knowledge of the pastoralists. This paper outlines effects of drought and coping mechanisms; discusses early warning system for pastoralists and early warning system for monitoring livestock nutrition, and verification of diet quality predictions including grazing land verification and field verification.